Surviving and flourishing in a neoliberal world: primary trainees talking. (29th November 2012) - Passy, Rowena
<x xml:space="preserve">Abstract</x> This article examines the ways in which the context of teaching shapes teachers' perceptions of their work. Its starting point is the seminal work of Nias, who argued from research conducted in the 1970s and 1980s that the particular historical context of the time in England encouraged teachers to be socialised into a tradition of isolation, individualism and a belief in personal autonomy. Nias theorised her findings in terms of the situational and substantial self, and I suggest that this particular environment encouraged the teachers' substantial self to be dominant. I then examine how the context for teaching has changed with the introduction of neoliberal reforms from the 1980s and, drawing on data from a qualitative project that has been investigating the characteristics and values of a small number of successful teacher trainees, argue that these participants' situational self is dominant in the teaching placements, where they have to show competence in 33 professional standards in a number of different schools to pass the course. However, as Nias's teachers, these teacher trainees want to be employed in a school in which they 'fit in' with the prevailing values, reinforcing the importance of school context in supporting and developing teachers' long term commitment to the profession.